1998
DOI: 10.1002/chin.199833181
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Rapid Entry to Highly Substituted 4,5‐Dihydronicotinonitriles.

Abstract: Rapid Entry to Highly Substituted 4,5-Dihydronicotinonitriles.-The one-pot preparation of the title compounds such as (III), (V), and (IX) by simple condensation of salicylaldehyde with malononitrile and aromatic heterocyclic ketones or by condensation of 2-imino-3-cyanocoumarins (I) with active methylene compounds in the presence of ammonium acetate is described. -(EL-AHL, A. A. S.; AFEEFY, H.; METWALLY, M. A.; Rev.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Further studies showed that increasing the amount of sodium stearate could improve the reaction significantly. Inspired by the result, we have changed the catalyst amount from 1 to 12 mol %, finding that 10 mol % of sodium stearate was good enough (Table 1, entries [14][15][16][17].…”
Section: Resultsmentioning
confidence: 98%
“…Further studies showed that increasing the amount of sodium stearate could improve the reaction significantly. Inspired by the result, we have changed the catalyst amount from 1 to 12 mol %, finding that 10 mol % of sodium stearate was good enough (Table 1, entries [14][15][16][17].…”
Section: Resultsmentioning
confidence: 98%
“…Isatin and a number of its derivatives posses a reactive carbonyl group that readily undergoes condensation reactions under mild conditions . It was therefore suitable as a precursor for the synthesis of heterocycles incorporating spiro indolines for pharmacological evaluation , medicinal application as muscle relaxants, and anti‐inflammatory agents .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the reaction of 2 with arylazoaminopyrazoles [12, 13], 2‐mercaptobenzazoles [14], thiocarbohydrazide, and thiocarbazones [15] as well as N ‐arylisoindolines [16] have been reported. Closely analogous 3‐(dicyano‐methylene)‐2‐indolone ( 3 ) [17] which is a ylidene malononitrile like 2 reacted with thiobarbituric acid [18], S,S ‐ and N,S ‐acetals [19], cyclohexanedione [20], and another active methylene systems to give spirohetero‐cyclic compounds [21, 22]. The reaction of N,N ′‐diarylacetamidines with 2 afforded indenoazepine‐6‐ones [23].…”
Section: Introductionmentioning
confidence: 99%